THE INFLUENCE OF PROFITABILITY RATIOS, DER, PBV, AND COVID19 ON STOCK RETURNS - Lee, Albert; Yulfiswandi, Yulfiswandi (Jurnal Keuangan dan Bisnis, 2024)
Investment is one of the activities that influences the growth of the Indonesian economy. Investment not only helps in economic development in Indonesia but also helps companies optimize their growth and provide a good response to investors. Investors have the main goal, namely achieving high returns or stock returns. However, high returns can also carry high risks, because shares have no certainty that they will rise or fall quickly and suddenly. Sudden changes in stock prices play an important role in determining stock prices and returns which can rise or fall very sharply so that they can create uncertainty for investors in making decisions to invest in a stock. The aim of this research is to determine the effect of PBV, ROE, NPM, EPS, DER, COVID on stock returns. To find out what factors cause what, this research uses a comparative causal research strategy. Companies in the Financial sector (consisting of 106 shares) which are included in the Composite Stock Price Index (also called IHSG) are the focus of this research. Data is taken from the application (Stockbit), in obtaining financial data. that researchers will use (idx.co.id). PBV has a positive effect on stock returns. Meanwhile, ROE, NPM, EPS, DER, COVID have no effect on stock returns